COLOUR STABILITY OF COMPOSITE RESINS IN THE PRESENCE OF HERBAL TEAS: A SPECTROPHOTOMETRIC STUDY - S., GOWRISH; SADANANDA, VANDANA; ZAKIYUDDIN, MURTAZA HATIM (International Journal of Applied Pharmaceutics, 2025)
Objective: This study aimed to evaluate and compare the effects of four herbal teas, Amla (Emblica officinalis), Hibiscus (Hibiscus sabdariffa), Moringa (Moringa oleifera), and Tulsi (Ocimum sanctum) on the colour stability of three composite restorative materials, nanohybrid composite resin, bulk-fill flowable composite and nanohybrid composite resin with SphereTEC fillers, over 60 d using spectrophotometric analysis. Methods: A total of 150 disc-shaped composite specimens were fabricated and divided into three groups: Nanohybrid composite resin (Group I), bulk-fill flowable composite (Group II) and nanohybrid composite resin with SphereTEC fillers (Group III). Each group was further divided into five subgroups (n=10), which were immersed daily in Amla, Hibiscus, Moringa, Tulsi tea, and in artificial saliva (control), for 15 min over 60 d. Colour changes were assessed at baseline, day 30, and day 60 using a digital reflectance spectrophotometer, and ΔE* values were calculated according to the CIELAB system. Results: At day 60, Tulsi tea induced the highest discolouration across all composite resins, with mean ΔE values of 36.21±0.37 (Group I), 37.39±0.40 (Group II), and 37.83±0.60 (Group III). Hibiscus and Amla teas also produced notable staining (ΔE up to 34.29), while Moringa tea caused the least discolouration (ΔE ≈ 30). The artificial saliva subgroups remained near baseline (ΔE<30). No statistically significant differences (p > 0.05) were observed between composite resin types, indicating that resin matrix hydrophilicity may play a more dominant role than filler morphology in staining susceptibility. Conclusion: Herbal teas demonstrated a potential for staining composite restorative materials, with Tulsi tea showing the greatest discolouration effect. These findings highlight the importance of material selection and patient counselling regarding dietary habits to maintain the aesthetic longevity of dental restorations.